Avaliação bioquímica e imunohistoquímica dos efeitos subletais do tiametoxam sobre Apis mellifera (Hymenoptera, Apidae) - Tavares, Daiana Antonia [UNESP] (2015)
The honeybee Apis mellifera have the economic and ecological importance, because they are pollinators of agricultural crops and natural areas, apart from the fact that the products and by-products of the colony are marketed. In recent decades, there has been an increase in global agricultural production and consequently a greater use of insecticide used to combat insect pests. Among the insecticides, the neonicotinoids stand out, widely used by its efficient, systemic action in plants. The thiamethoxam insecticides that belongs to this class acts as an agonist at nicotinic acetylcholine receptors in the central nervous system of insects. However, thiamethoxam can also affect non-target insects such as bees. Once the forage bees can collect contaminated pollen and nectar, and store inside the colony, both adult bees and larvae, which depend on food resources provided by workers, may also be contaminated. The objectives of this study were to evaluate the toxicity of thiamethoxam in the post-embryonic development of A. mellifera, as a result of larval exposure to this pesticide, and analyze the sublethal effects of this insecticide in post-embryonic stages, the survival, the enzymatic activity acetylcholinesterase (AChE), glutathione-S-transferase (GST), carboxylesterase (CaEs) and alkaline phosphatase (PAL), as well as to evaluate the levels of the protein synapsin in the brain. Bioassays were made acute larval exposure thiamethoxam, by contact or ingestion. After 48 hours of exposure topical to thiamethoxam, there was an increase in mortality in a dose of 15 ng/μL and also effects on pupation and emergence of bees, especially at a dose of 500 ng/μL. Were observed changes in the survival of larvae exposed orally to sublethal dose of 1.44 ng/μL, and pupae in the pre-exposed to 1.44 and 0.001 ng/uL, with consequent reduction in the percentage emerging honeybees. Sublethal effects were observed by increasing the enzyme activity of AChE in ...